Output Losses in Europe During COVID-19 : What Role for Policies? - Ari, Anil (IMF Working Papers; Working Paper ;, 2022)
We use a decomposition methodology to analyze the factors underlying the differentiated output losses of European countries in 2020. Our findings are fourfold: First, 2020 growth outcomes can be explained by differences in mobility, underlying growth trends, and pre-pandemic country fundamentals. Second, fiscal and monetary policies helped alleviate output losses during the pandemic in all European countries but to a varying extent. Third, shallower recessions in emerging market economies in Europe can be attributed to higher underlying growth and younger populations. Fourth, fiscal multipliers were higher in countries where above-the-line measures accounted for a larger share of the total fiscal package, the size of the total fiscal package was smaller, and inequality and informality were greater, as well as in countries with IMF-supported program during the pandemic.